Two rare cases of pituitary apoplexy in adult females: a tricky diagnosis - Tupputi, Umberto; Testini, Valentina; Manco, Maria Grazia Rita; Paparella, Maria Teresa; Bellitti, Roberto; Guglielmi, Giuseppe (Acta Biomedica Atenei Parmensis, 2023)
We reported two cases of women who suffered from a rare case of pituitary apoplexy, rare and potentially fatal clinical condition due to a hemorrhagic infarction of the pituitary gland due to a pre-existing macroadenoma.The onset of symptoms is often insidious and includes generic symptoms such as headache, vomiting, and visual disturbances.In this case report we discuss the typical CT and MRI imaging features of this rare clinical condition in order to help radiologists in the timely diagnosis for a more rapid and correct diagnostic framing.